FILOSOFI, IDEOLOGI DAN PARADIGMA PENDIDIKAN ISLAM INTER, MULTI DAN TRANSDISIPLINER - Indra Wijaya; Syaifuddin Sabda (STAI AL FALAH Banjarbaru, 2023)
AbstractIn general, the design philosophy of Islamic education is not much different from other education. Namely, it includes ontology, epistemology and axiology. However, after researching, parsing and drawing conclusions, several fundamental differences were found between these philosophical structures. For example, from an epistemological perspective, Islamic education is based on the Koran and hadith/sunnah. From the aspect of ontology, the philosophy of Islamic education does not only focus on a real (real) reality but also un-real-abstract. Meanwhile, from the axiological aspect, the philosophy of education does not only refer to one value point of view but refers to several points of view, including human values (moral), as well as divine values (religion) and so on.The diversity of ethnicities, religions and cultures is a fact of Indonesian history. Diversity can be a gift or a disaster. If managed properly it can enrich human life; conversely, if it is not managed properly it can lead to disasters in the form of tension, conflict, and violence. The function of Islamic Religious Education as a subject that is still preserved in the National Education System is expected to shape the character of students, so that they become pious Muslims (in the sense of obedience to Allah), and at the same time become citizens. Indonesia that is tolerant, accepts multicultural conditions, and rejects all forms of oppression that demean human dignity. Specifically, it can be seen from the learning objectives, namely realizing Indonesian people who are religious, have noble character, are knowledgeable, diligent in worship, intelligent, productive, honest, fair, ethical, disciplined, tolerant (tasamuh), maintain harmony and develop religion. culture at school. Philosophically, Islamic education is relevant and an integral part of the national education system. The position of Islamic education as a national education subsystem does not only function as a complement, but as a substantial component. That is, Islamic education is an important component in the journey of national education. Because the government has proposed the concept of multicultural education, civic education, and character education, Islamic education cannot be separated from it. Keywords: Ideology, Paradigm of Islamic Education, Philosophy. AbstrakSecara umum, rancang bangun filosofi pendidikan Islam tidak jauh berbeda dengan pendidikan lainnya. Yakni, mencakup ontologi, epistemologi dan aksiologi. Namun setelah diteliti, diurai dan diambil suatu simpulan, ditemukan beberapa perbedaan yang mendasar antara bangunan filosofi tersebut. Misalnya, dari aspek epistemologi, pendidikan Islam berlandaskan pada al-Qur‟an dan hadith / sunnah. Dari aspek ontologi, filosofi pendidikan Islam tidak hanya fokus pada suatu realitas yang riil (nyata) tapi juga un-riil-abstrak. Sedangkan dari aspek aksiologi, filosofi pendidikan tidak hanya mengacu kepada satu sudut pandang nilai tapi mengacu pada beberapa sudut pandang, diantaranya adalah nilai-nilai kemanusiaan (moral), maupun nilai ketuhanan (agama) dan lain sebagainya. Kemajemukan suku, agama, dan budaya merupakan fakta sejarah Indonesia. Keanekaragaman bisa menjadi hadiah atau bencana. Jika dikelola dengan baik dapat memperkaya kehidupan manusia; sebaliknya jika tidak dikelola dengan baik dapat menimbulkan bencana berupa ketegangan, konflik, dan kekerasan. Fungsi Pendidikan Agama Islam sebagai mata pelajaran yang masih dilestarikan dalam Sistem Pendidikan Nasional diharapkan dapat membentuk karakter peserta didik, sehingga menjadi muslim yang bertakwa (dalam arti taat kepada Allah), dan sekaligus menjadi warga negara. Indonesia yang toleran, menerima kondisi multikultural, dan menolak segala bentuk penindasan yang merendahkan harkat dan martabat manusia. Secara khusus dapat dilihat dari tujuan pembelajaran, yaitu mewujudkan manusia Indonesia yang agamis, berakhlak mulia, berilmu, rajin beribadah, cerdas, produktif, jujur, adil, beretika, disiplin, toleran (tasamuh), menjaga kerukunan dan mengembangkan agama. budaya di sekolah. Secara filosofis, pendidikan Islam relevan dan merupakan bagian integral dari sistem pendidikan nasional. Kedudukan pendidikan Islam sebagai subsistem pendidikan nasional tidak hanya berfungsi sebagai pelengkap, tetapi sebagai komponen yang substansial. Artinya, pendidikan Islam merupakan komponen penting dalam perjalanan pendidikan nasional. Karena pemerintah telah mengajukan konsep pendidikan multikultural, pendidikan kewarganegaraan, dan pendidikan karakter, maka pendidikan Islam tidak bisa lepas darinya. Kata Kunci: Filosofi, Ideologi, Paradigma Pendidikan Islam.